SOCIAL PORTRAIT OF THE SHORT STORY "RUMAH IBU" BY HARRIS EFFENDI THAHAR - Muhamad Burhanudin; Aqilla Elza Dinasti (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
The purpose of this article is to reveal social criticism in a short story. The object that will be the center of the study is the short story Rumah Ibu by Harris Efendi Thahar. This short story carries a social theme in family life after his father died. The method used is a qualitative description method. Qualitative research intends to understand the phenomena experienced by research subjects. The author obtains data using reading and note-taking techniques and uses a sociological approach to literature with Swingewood theory, which focuses on literature as a reflection of the times. Sociology of literature is a science that describes the relationship between humans at the social level but is still within the scope of literature. The results showed that in the short stories Rumah Ibu found several portraits of social criticism which were grouped into: moral portrait, religious portrait, technology portrait, and portrait of family.